Past and Present Proposed Amendments to the United States Constitution Regarding Marriage - Edward Stein (Washington University Law Quarterly, 2004)
Proposals to amend the Constitution to prohibit same-sex marriage were recently actively discussed and voted on in the U.S. Congress. This Article situates arguments for these proposals within the history of attempts to amend the Constitution related to marriage by providing the first detailed, synthetic analysis of such previously proposed amendments. This examination reveals 133 previously proposed amendments to the Constitution relating to marriage, consisting primarily of proposals to prohibit interracial marriage, proposals to prohibit polygamy, and proposals to empower Congress to make uniform laws concerning marriage and divorce. By tracing the arguments made in support of these amendments, this Article reveals a strong resonance between prior attempts to constitutionalize aspects of the institution of marriage and current proposed amendments. The Article also argues that, in hindsight, the previously proposed amendments were not necessary because state and federal legislatures and courts were able to address problems relating to marriage without amending the Constitution and without destabilizing the delicate balance of power between states and the federal government. Against this background, the Article concludes that current proposals to amend the Constitution are similarly neither necessary nor wise.
Keywords: Same-sex marriage; Constitutional amendments; Federal government; Marriage law; Polygamy